2016
DOI: 10.1007/s11274-015-1989-9
|View full text |Cite
|
Sign up to set email alerts
|

Selection and characterization of Argentine isolates of Trichoderma harzianum for effective biocontrol of Septoria leaf blotch of wheat

Abstract: Species of the genus Trichoderma are economically important as biocontrol agents, serving as a potential alternative to chemical control. The applicability of Trichoderma isolates to different ecozones will depend on the behavior of the strains selected from each zone. The present study was undertaken to isolate biocontrol populations of Trichoderma spp. from the Argentine wheat regions and to select and characterize the best strains of Trichoderma harzianum by means of molecular techniques. A total of 84 out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
4
0
4
Order By: Relevance
“…Trichoderma harzianum isolates T4 and T2 showed the greatest effectiveness for controlling disease, with similar reduction values to that shown by the fungicide (Folicur) application treatment (Perello et al, 2009). Stocco et al (2016) characterized 240 isolates of Trichoderma harzianum from the Argentine wheat regions by means of molecular techniques and selected 37 strains which reduced the severity of Septoria leaf blotch 50%. These 37 native strains of T. harzianum are important in biocontrol programs and could be advantageous for the preparation of biopesticides adapted to the agroecological conditions of wheat culture.…”
mentioning
confidence: 80%
“…Trichoderma harzianum isolates T4 and T2 showed the greatest effectiveness for controlling disease, with similar reduction values to that shown by the fungicide (Folicur) application treatment (Perello et al, 2009). Stocco et al (2016) characterized 240 isolates of Trichoderma harzianum from the Argentine wheat regions by means of molecular techniques and selected 37 strains which reduced the severity of Septoria leaf blotch 50%. These 37 native strains of T. harzianum are important in biocontrol programs and could be advantageous for the preparation of biopesticides adapted to the agroecological conditions of wheat culture.…”
mentioning
confidence: 80%
“…Application of culture filtrates and spore suspension of T. harzianum reduced the size of necrotic spots of black scorch disease of date palm caused by Ceratocystis radicicola (Al-Naemi et al, 2016). T. harzianum is also known to reduce severity of leaf blotch of wheat caused by Zymoseptoria tritici (Stocco et al, 2016). The modes of action of Trichoderma are competition, antagonism and production of certain antifungal compounds (Nederhoff, 2001).…”
Section: Pot Trialmentioning
confidence: 99%
“…Management of plant pathogens by biological means is considered an alternative environment friendly strategy for sustainable agriculture (Al-Naemi et al, 2016;Youssef et al, 2016). Trichoderma is among the most commonly used biocontrol agents and is an effective antagonist against plant pathogenic fungi ( Kumar and Mukerji, 1996;Stocco et al, 2016). Recent studies have shown that Trichoderma spp., especially T. harzianum, can control diseases caused by Rhizoctonia solani, Macrophomina phaseolina and Ceratocystis radicicola (Al-Naemi et al, 2016;Javaid et al, 2017b;Youssef et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…• disminución de la severidad de la mancha de la hoja en trigo causada por Zymoseptoria tritici (Stocco et al, 2016).…”
Section: Trichoderma Como Pgpmunclassified
“…Las múltiples funciones de Trichoderma en las asociaciones planta-Trichoderma son de particular importancia para la sustentabilidad de los ecosistemas tanto naturales como agrícolas. La aplicabilidad de los aislamientos de Trichoderma a diferentes ecozonas depende del comportamiento de las especies seleccionadas en cada una de ellas y, como ya se ha mencionado durante este trabajo de tesis, los mejores aislamientos podrían seleccionarse de áreas de la planta y del suelo donde se espera que funcionen mejor como PGPM y donde crezcan en condiciones ecológicas similares a las que se encuentran en forma natural (Stocco et al, 2016). Diferentes especies de Trichoderma pueden exhibir variación en la actividad como PGPM, lo que hace que un estudio específico de su biodiversidad sea esencial para aprovechar al máximo el potencial de estos microorganismos (Hoyos-Carvajal & Bissett, 103 2011).…”
unclassified